2016
DOI: 10.1007/s11064-016-2056-0
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1-Receptors Modulate mTOR Signaling to Regulate White Matter Inflammatory Lesions Induced by Chronic Cerebral Hypoperfusion

Abstract: We sought to investigate the role of the adenosine A1 receptors (A1ARs) in white matter lesions under chronic cerebral hypoperfusion (CCH) and explore the potential repair mechanisms by activation of the receptors. A right unilateral common carotid artery occlusion (rUCCAO) method was used to construct a CCH model. 2-chloro-N6-cyclopentyladenosine (CCPA), a specific agonist of A1ARs, was used to explore the biological mechanisms of repair in white matter lesions under CCH. The expression of mammalian target of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Emerging evidence has indicated that CCH is associated with an increased inflammatory response in the brain. 15 , 16 This may be a consequence of Aβ formation and tau hyperphosphorylation induced by CCH. 17 , 18 Although the inflammatory response is crucial for the brain to remove senescent cells and extrinsic pathogenic substances, long-lasting neuroinflammation is toxic to neurons and synapses, and thus contributes to neurodegeneration, white matter damage and cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that CCH is associated with an increased inflammatory response in the brain. 15 , 16 This may be a consequence of Aβ formation and tau hyperphosphorylation induced by CCH. 17 , 18 Although the inflammatory response is crucial for the brain to remove senescent cells and extrinsic pathogenic substances, long-lasting neuroinflammation is toxic to neurons and synapses, and thus contributes to neurodegeneration, white matter damage and cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The same process without carotid ligation was operated on the sham group. Body temperature was sustained until mice were woken from anesthesia [39][40][41][42][43].…”
Section: Animalsmentioning
confidence: 99%
“…The effects of anti-apoptosis and promoting oligodendrocytes proliferation, increasing myelin gene expression lead PI3K/Akt/mTOR pathway as one of essential signaling pathways during myelin growth [ 17 ]. Several studies showed that PI3K/Akt/mTOR signalings involved in white matter injuries after chronic cerebral hypoperfusion in rats [ 18 - 20 ].…”
mentioning
confidence: 99%